PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO SEPATU BATA MTC GIANT PANAM PEKANBARU - Hacika Arina Putri; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at MTC Giant Panam Pekanbaru Brick Shoe Store, located on HR street. Soebrantas KM. 12.5. The purpose of this research is to find out the influence of brand image and product quality on purchasing decisions on consumers who shop at MTC Giant Panam Pekanbaru Brick Shoe Store. Where brand image as variable (X1), product quality as variable (X2), and purchase decision as variable (Y).The research method used is descriptive quantitative analysis obtained from questionnaire results and measured by likert scale which is then processed with SPSS version 23. Samples in this study as many as 100 respondents from the population were calculated using the formula slovin. The study used simple linear regression analysis methods and multiple linear regression analysis.The technique used in this study was Accidental Sampling. The results of the analysis showed that brand image variables and product qualityhad a positive and significant influence on the increase in purchasing decisions both partially and simultaneously.Keywords: Brand Image, Quality, Purchasing Decision